Hyperglycemia Inhibits Complement-Mediated Immunological Control of S. aureus in a Rat Model of Peritonitis - Clifford T. Mauriello; Pamela S. Hair; Reuben D. Rohn; Nicholas S. Rister; Neel K. Krishna; Kenji M. Cunnion (Journal of Diabetes Research)
Hyperglycemia from diabetes is associated with increased risk of infection from S. aureus and increased severity of illness. Previous work in our laboratory demonstrated that elevated glucose (>6 mM) dramatically inhibited S. aureus-initiated complement-mediated immune effectors. Here we report in vivo studies evaluating the extent to which a hyperglycemic environment alters complement-mediated control of S. aureus infection in a rat peritonitis model. Rats were treated with streptozocin to induce diabetes or sham-treated and then inoculated i.p. with S. aureus. Rats were euthanized and had peritoneal lavage at 2 or 24 hours after infection to evaluate early and late complement-mediated effects. Hyperglycemia decreased the influx of IgG and complement components into the peritoneum in response to S. aureus infection and decreased anaphylatoxin generation. Hyperglycemia decreased C4-fragment and C3-fragment opsonization of S. aureus recovered in peritoneal fluids, compared with euglycemic or insulin-rescued rats. Hyperglycemic rats showed decreased phagocytosis efficiency compared with euglycemic rats, which correlated inversely with bacterial survival. These results suggest that hyperglycemia inhibited humoral effector recruitment, anaphylatoxin generation, and complement-mediated opsonization of S. aureus, suggesting that hyperglycemic inhibition of complement effectors may contribute to the increased risk and severity of S. aureus infections in diabetic patients.